The effect of the percentage of syllables stuttered, attention, and perfectionism on listener’s comprehension scores - Cangi, M. Emrah; Dölek, Muhsin; Çavdar, Derya (Revista de Investigación en Logopedia, 2023)
The primary aim of this study was to compare the listening comprehension levels of four groups of people who listened to recordings that varied in terms of the percentage of syllables stuttered (%SS). The secondary aim was to examine the effects of %SS, attention/hyperactivity, and perfectionism on comprehension. Sixty-four fluent participants between the ages of 18-40 were randomly assigned to gender-equivalent four groups. All participants completed ADHD and perfectionism scales. A clinician read aloud a text, exhibiting different levels (0%, 5%, 10%, and 15%) of %SSs (speech naturalness r>0.800). Each group of participants listened to a recording with a different %SS level. The comprehension performance was evaluated with the Listening Comprehension Assessment Tool developed by the authors. The validity measures of the tool were sufficient for teachers and clinicians (X̅>0.800). The group that listened to the fluent (0%) recording scored significantly higher than the other groups on mean comprehension scores. Covariance analysis indicated that only the %SS level significantly affected the comprehension score.